2008
DOI: 10.1007/s10072-008-1042-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and therapy for neurogenic bladder dysfunctions in multiple sclerosis patients

Abstract: Neurogenic lower urinary tract dysfunctions are common in patients with multiple sclerosis and for most of them urinary dysfunction has the most negative impact on their social life. No correlation exists between clinical urinary symptoms and urodynamic patterns. Abnormal urodynamic patterns may be present in asymptomatic patients. Both clinical and urodynamic findings may change during the course of the illness. Early diagnostic approach and scheduled follow-ups are mandatory in order to prevent upper urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…1 MS patients frequently suffer from urinary complaints. [2][3][4] De Seze and colleagues 5 report a prevalence of 37-99% for overactive bladder syndromes, characterized by irritative bladder symptoms, a prevalence of 34-79% for obstructive symptoms and 25% for chronic urinary retention.…”
Section: Introductionmentioning
confidence: 99%
“…1 MS patients frequently suffer from urinary complaints. [2][3][4] De Seze and colleagues 5 report a prevalence of 37-99% for overactive bladder syndromes, characterized by irritative bladder symptoms, a prevalence of 34-79% for obstructive symptoms and 25% for chronic urinary retention.…”
Section: Introductionmentioning
confidence: 99%
“…However, bladder dysfunction can be prevented or symptomatically treated through various strategies, including pharmacologic therapies and behavioral approaches. [25][26][27][28][29][30][31] Del Popolo et al 29 concluded that behavioral rehabilitation and conservative treatments for bladder dysfunction are sufficient for most MS patients, with innovations in neurourology improving urologic function and QOL for patients not responding to firstline treatments. Options for bladder management in MS care have improved, and more patients are receiving effective treatment, with bladder problems often treated at the same clinic providing neurologic care.…”
Section: Bladder Dysfunctionmentioning
confidence: 99%
“…5,6 Although our patient had no neurological symptoms and no pathological neurological finding on physical examination, we performed cranial and lumbosacral magnetic resonance imaging to exclude neurogenic causes of atonic bladder. Neither multiple sclerosis nor lumbar disc protrusion or cauda equina syndrome was detected.…”
Section: Discussionmentioning
confidence: 94%